Speculative Finance and Network Temporality in Duncan Jones's Moon and Source Code. - Pierson, David P. (CR: The New Centennial Review)
The article examines how certain science fiction films make the invisible operations of finance visible. Topic covered include Duncan Jones's two science fiction films "Moon" and "Source Code," the ways that speculative finance and network time alter the basic sense of temporality, and the ways in which speculative finance commoditizes risk and leverages assets to build a perpetual present calculated for riskless flows of capital.